COVID-19 pandemic and mental healthcare: Impact on health insurance with guaranteed universal access in Chile - Toro-Devia, Olga; Leyton, Gonzalo (Frontiers in Public Health, 2023)
Background Universal health coverage (UHC) is a goal of the member states of the United Nations. The negative impact of the COVID-19 pandemic on mental health, inequalities in access to care, and financing gaps set a problematic scenario for universal mental health coverage. In Latin America, depression and anxiety disorders have increased by more than 30%. Chile implemented a reform for UHC in 2005 generating a mandatory guaranteed plan for health insurance (GES) that covers schizophrenia, depression, bipolar disorders, and Alzheimer's disease. We assume that the pandemic increased cases of mental illness in GES of public and private insurance. Objectives This study aimed to explore the effects of the pandemic on the use of the GES mental health plan of public and private insurance. Methods A descriptive analysis of secondary data from public and private insurance on the use and expenditure of the GES plan in mental illness between 2005 and 2020 was carried out. An aggregate analysis of the use of psychiatric consultations without a guaranteed plan and sick leave was performed. Results Between 2005 and 2020, 18.5% of GES cases corresponded to four mental health illnesses (1,682,021 cases). Public insurance covered 80% of cases. In the pandemic, cases of mental illness fell by 10.5% in public insurance and 28.7% in private ones, reducing spending by 33 and 6.2%, respectively. Psychiatric consultations without using the GES plan doubled in 2020 in private insurance, and medical discharges due to mental illness also increased. Leave due to mental illness increased by 20% in both types of insurance. Conclusion The results suggest that the demand for mental healthcare increased during the pandemic, but public and private health insurance reduced admissions to the GES universal plan for schizophrenia, depression, and bipolar disorder. A universal guaranteed plan in an individual contribution system can have essential weaknesses for people when the principles of social security are not complied with, especially concerning the solidarity of the health insurance system.